The Role of Stakeholders’ Collaboration in Eliminating Child Labor: A Case of Indonesia’s Agriculture Sector - Irma Tyasari; Abdul Wahab; Achmad Marzuki; Muhammad Yafie Zenas Asy’ari; Eka Aprilia Fo (Amirul Bangun Bangsa, 2023)
The goal of international labor Organization is to eliminate all forms of child labor since at the year of 2016 and it still needs to be supported until today. The aim of this program is to show how stakeholders’ collaboration and coordination have been focusing on the contribution and their roles to the reduction of child labor. The combination between field observation and interview to 20 NGO’s directors and field operating managers is the method used in this program. Although the collaboration’s efforts and the intervention of the stakeholders have been discussed in previous papers, however, its connection with socio- political view from NGO’s network perspectives and NGO’s network salience have not been sufficiently revealed, particularly in agriculture sector in Indonesia. The finding shows that the collaboration effects the capacity of network members through strengthening partnership for action against child labor, increasing the awareness and understanding of parents and farmers regarding child labor and its regulation, and developing a model of child-friendly village. This program has an implication to advocate for more supportive policies on child labor elimination and technical support for stakeholders both at national as well as regional level